The audit and its influence on the control of the activities carried out by the companies - Zambrano Montesdeoca, Lady Diana (2020)
Objective: To learn about the audit and its influence on the control of the activities carried out by the companies. Method: The focus of the study was quantitative, the type of research descriptive, correlational and exploratory; the non-experimental transectional design. A field investigation was carried out, with visits to companies, using surveys and learning about their reality; in turn, historical research was used, with which authentic information was obtained from the companies and the use of audits at the company level. Results: Audits influence the control of activities carried out by companies, as they can help entities improve their functionality and achieve significant cost savings. Conclusions: The present investigation managed to determine the current situation of the companies under study, knowing their strengths and weaknesses, which allowed us to know their operation, in order to verify the veracity of the audits in order to justify the use of their resources efficiently, confirming the importance of carrying out this type of meticulous and exhaustive control from time to time in organizations.